Regulatory unbundling in telecommunications - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2011)
Due to its dynamic nature, and the increasing importance of competitive sub-parts, the telecommunications sector provides particularly interesting insights for studying regulatory unbundling. Based on the theory of monopolistic bottle-necks the fallacies of overregulation by undue unbundling obligations are indicated. Neither the promotion of infrastructure competition by mandatory un-bundling of competitive subparts of telecommunications infrastructure, nor regulatory induced network fragmentation within monopolistic bottleneck com-ponents is justified. The impact of the shrinking of the areas of network specific market power on the remaining unbundling regulation is analyzed. Finally, the phasing-out potentials of unbundling regulation in European telecommunica-tions markets are pointed out.
Keywords: 330